2007
DOI: 10.1080/13697130701739118
|View full text |Cite
|
Sign up to set email alerts
|

Moderate alcohol consumption contributes to women's well-being through the menopausal transition

Abstract: Among women undergoing menopausal transition, well-being is positively associated with moderate alcohol consumption along with other lifestyle factors in a synergistic fashion, rather than any individual factor having a dominant or an independent effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
(36 reference statements)
0
5
0
1
Order By: Relevance
“…A positive association between moderate alcohol consumption and sexual activity/wellbeing of women in the menopause has been reported in other studies [21][22][23]. Apart from the disinhibiting or relaxing effect of alcohol, this factor could also be a marker for unmeasured characteristics of the sexually active women.…”
Section: Discussionmentioning
confidence: 53%
“…A positive association between moderate alcohol consumption and sexual activity/wellbeing of women in the menopause has been reported in other studies [21][22][23]. Apart from the disinhibiting or relaxing effect of alcohol, this factor could also be a marker for unmeasured characteristics of the sexually active women.…”
Section: Discussionmentioning
confidence: 53%
“…Prior outcomes have identified a moderate alcohol intake (when accompanied with physical exercise and absence of smoking behavior) as beneficial to menopausal women's well-being [36]. Although perceived loss of control is treated as a dependent variable in the present study, it would be pertinent to explore, in future researches, if subjective loss of control is a significant mediator of menopausal symptoms' severity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in a previous study, everyday stressful experiences had a negative impact in middle-aged women [36] and negative life events were presented as a risk factor for menopausal symptoms [2]. Specifically, negative events perceived as having an important impact in women's lives (as well as family dysfunction) incremented the risk for psychological symptoms: depression, anxiety and stress [3].…”
Section: Discussionmentioning
confidence: 99%
“…Data from prospective cohort studies and cross-sectional surveys also suggest that light to moderate alcohol consumption may protect against cognitive impairment and dementia in older adults (Bond et A prospective observational study found that among women undergoing menopausal transition, moderate alcohol consumption was one of a range of protective factors contributing to women's perceptions of general and emotional well-being, but that the effects of alcohol were different depending on the women's other lifestyle patterns (Alati et al 2007).…”
Section: Benefits Of Light To Moderate Drinking For Older Peoplementioning
confidence: 99%